Structural Characterization and Biocidal Studies of Some Nickel(II) Macrocyclic Complexes - Ambwani, Jitendra; Bansal, N.L.; Rani Sharma, Mamta (Asian Journal of Chemistry, 2010)
Two new macrocyclic complexes with formulae Ni(IDADH] (BF4)2 and Ni[TDPDH](BF4)2 {where [IDADH] = di-phenyldiacetic acid-N-imino diacetyl dihydtazone and (TDPDH) = diphcnyl diacetic acid-N-thio dipropionic acid dihydtazonc have been synthesized. These complexes have been scteened for their antibacterial and antifungal activities against certain specified microbial strains. viz ., bacterial strains S. auerus and E. coli and fungal strains A. niger and C. albicans. These complexes have been characterized using molar conductances, magnetic studies, elemental analysis and spectral (lR and electronic) studies. The complexes have been found to have octahedral structures. Both the complexes show greater biological activity than the ligand fragments, the activity effect being more against bacterial species and slightly less against fungal strains.